Ocorrência de diclofenaco e naproxeno em água superficial no município de Três Lagoas (MS) e a influência da temperatura da água na detecção desses anti-inflamatórios - Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Isique, William Deodato [UNESP]; Torres, Nádia Hortense; Machado, Angela Aparecida [UNESP]; De Carvalho, Sérgio Luís [UNESP]; Valério Filho, Walter Veriano [UNESP]; Ferreira, Luiz Fernando Romanholo (FapUNIFESP (SciELO), 2017)
The aims of this study were to evaluate the presence and concentration of the anti-inflammatory drugs diclofenac and naproxen in an urban stream located in Três Lagoas, Mato Grosso do Sul, Brazil, that receives effluent from a wastewater treatment plant; and to evaluate the influence of water temperature in the occurrence of these drugs into surface waters. Monitoring of both anti-inflammatory and the parameters temperature, pH and dissolved oxygen was held in this water body during 12 consecutive months (October 2008 to September 2009). Water samples were collected monthly at six points representing different sections of the stream. The samples were subjected to solid phase extraction procedure and analyzed by high performance liquid chromatography. To check the influence of water temperature on the occurrence of the anti-inflammatory drugs diclofenac and naproxen in aquatic environments, it was used a logistic model of regression, the Statistical Analysis System version 9.0. The anti-inflammatory drugs diclofenac and naproxen were detected at different points in the Stream of Onça. The other parameters evaluated in this study were compared with the water quality standards established by the CONAMA Resolution 357/2005. The highest concentration of diclofenac was detected in the point located downstream of the wastewater treatment plant of the city, while the largest concentration of naproxen was recorded at the mouth of the stream. The water temperature influence, in an inversely proportional way, the occurrence of both anti-inflammatory in the stream, the higher the temperature the lower the water body probability of detection of drug diclofenac and naproxen.
Occurence of diclofenac and naproxen in surface water in the Três Lagoas (MS) city and water temperature influence in the detection of these anti-inflammatories
Keywords: Drug; Wastewater treatment plant; Water body